THE APPLICATION OF RESILIENT ARCHITECTURE CONCEPT IN THE OCEANARIUM DESIGN IN PARANGTRITIS - Bidari Putri Rosadi; Agung Kumoro Wahyuwibowo; Hardiyati Hardiyati (Universitas Sebelas Maret Surakarta, 2019)
Indonesia has a huge diversity of marine biota but there is degradation based on IUCN Red List. In this case, the preservation of marine biota is necessary. Besides that, Yogyakarta has a big potential to develop the maritime tourism especially in Parangtritis Beach. However, the location is susceptive with the external interferences like earthquake, windstorm, and tsunami. Therefore, it is necessary to build oceanarium which can protect the marine biota with three functions; recreation, education, and preservation. Furthermore, the design of oceanarium uses the resilient architecture approach that is adaptive towards the external interferences (earthquake, windstorm, and tsunami). The method which is used is descriptive qualitative with case study of resilient architecture literature, physical condition of site and government regulation. The application of resilient architecture is applied to five aspects of design; site (evacuation access, minimum height, and assembly point), form and mass (modification and circle application), building appereance (material that has durability), structural systems (construction system that withstands earthquake and tsunami). The analysis process produces an oceanarium design that accommodates marine biota and adaptive towards the external interferences (earthquake, windstorm, and tsunami).